The technological trajectory of integrated pest management for rice in Cambodia - Flor, Rica; Chhay, Kry; Sorn, Vichet; Maat, Harro; Hadi, Buyung (MDPI, 2018)
For the past two decades, while the efficacy of Integrated Pest Management (IPM) has been successfully demonstrated in Cambodia, its dissemination and sustained adoption among farmers have not met similar success. This study moves away from simplistic analyses about constraints in extension methods for IPM. Instead, we take a broader look into technological systems and the trajectory for pest management, which affected the spread and uptake of IPM in the country. Through a review of the wider context in policies and programs, and a survey of farmers from five provinces in Cambodia (N = 400), we examined the connections between options for pest management at the farmer level and conditions in the technological system. Using the Cambodian case study, we show that the technological system predisposes to pesticide use and as such hinders a trajectory of IPM. Systemic conditions, including interrelated agronomic practices, ecological conditions in farming communities, governance mechanisms, structures around the spread of knowledge and the industry around the technological options, have created mutual socio-technical dependencies. Although programs targeted change through knowledge of IPM, much of the systemic conditions sustain the trajectory of pesticide reliance. Hence, promoting an innovation environment that is supportive of IPM requires extension beyond knowledge dissemination, addressing these varied elements of the technological system.